An Adult Case of Medulloblastoma with Multiple Lung Metastatic Lesions—Case Report and Literature Review - Azab, Mohammed A. (Asian Journal of Neurosurgery, 2024)
Medulloblastoma (MB) cerebelli is a common brain tumor of the childhood. MB commonly spreads through cerebrospinal fluid; however, there are several reported cases of extracranial spread. The most common sites of extracranial metastasis are bones and bone marrow followed by peritoneum, liver, and lungs. Here, we report a case of pulmonary metastatic lesions of adult cerebellar MB that were discovered 1 year after the primary surgical treatment. We also tried to highlight similar reported cases in the literature.
Keywords: medulloblastoma; adult; leptomeningeal spread; lung metastasis